Implementation of Integrated Educational Management System at Vocational High Schools (A Study Comparative SMKN 1 and SMKN 2 Lhokseumawe City) - Akhyar, Akhyar; Ilham, Muhammad (Development: Studies in Educational Management and Leadership, 2022)
The study investigated the implementation of integrated management systems in SMK 1 and SMK 2 Lhokseumawe. The research aims to identify the application of management systems in the two schools. A qualitative method with a descriptive-analytic approach was used for the study. Data collection techniques included interviews and observation. The study found that several applications such as Google Classroom, WhatsApp, Google Meet, and Teacher Room App can be utilized by SMK 1 and SMK 2. In addition to using applications, both schools also use websites and social media as information platforms for all information management systems.